Acute and subacute oral toxicity assessment of Gancao Xiexin decoction in Sprague-Dawley rats - Ru, Li; Liu, Ruotong; Xing, Haoyu; Yuan, Yueming; Yuan, Zheng; Xu, Zhiyong; Xu, Qin; Song, Jianping; Li, Xiaobo (Frontiers in Pharmacology, 2023)
Gancao Xiexin decoction (GCXXD), a well-known classic traditional Chinese medicine prescription, is used to treat various oral ulcers, Behcet disease, gastrointestinal ulcers, etc. However, there is very little information on its safety. This study aimed to investigate the acute and subacute oral toxicity of GCXXD in Sprague-Dawley rats. In the acute toxicity study, rats were orally administered 10 g/kg GCXXD three times a day. Clinical signs of abnormality and mortality were observed daily for 14 days. In the subacute toxicity study, rats were orally administered 0, 1.47, 3.83, or 10 g/kg GCXXD for 28 days. The rats’ clinical signs, body weight, food consumption, hematological and biochemical parameters, bone marrow smear, organ index, and pathological morphology were analyzed. The acute toxicity study showed that GCXXD is safe in rats without any obvious toxicity via an oral dose of 30 g/kg/day (3×10 g/kg). After 28 days of administration, slightly decreased RBC, HGB, and HCT were observed in female rats at 10 g/kg, suggesting that repeated doses of high-dose GCXXD may cause mild anemia in female rats. The no-observed-adverse-effect level (NOAEL) and lowest-observed-adverse-effect level (LOAEL) of oral administration of GCXXD for 28 days in rats are considered to be 3.83 g/kg and 10 g/kg, respectively. Long-term toxicity studies are recommended to strengthen the findings.